Сutaneous Vasculitis: Classification, Diagnosis and Differential Diagnosis (Part 2) - Vladislav R. Khairutdinov; Irena E. Belousova; Aleksey V. Samtsov (State Scientific Center of Dermatovenereology and Cosmetology, 2020)
This article is a continuation of the literature review on skin vasculitis. In the first part, information was presented on the current nomenclature and prevalence of vasculitis, pathomorphological changes in the skin, as well as diagnostic algorithms for examining patients with this pathology are reflected. The second part of the article contains a detailed description of the elements of the skin rash with systemic and organ-specific vasculitis, presents the clinical manifestations observed with damage to other organs and systems, the development of possible complications. The data on modern treatment tactics are summarized, modern approaches using pathogenetic and symptomatic therapy of patients with various vasculitis are reflected.